Development of a computer aided software for power transmission shaft design with multiple criteria (2010)
Power transmission shafts, such as the crankshaft, impeller shaft, propeller-shafts, camshafts etc, are essential machine elements with wide application in mechanical systems. The manual shaft design procedure is known to be tedious and complex becajuse of large numbers of formulas, many computations and iteration procedures involved in the design. However, the use of Computer Aided Software (CAS) offers improved accuracy, high speed computations, reduced rigorousness and cumbersomeness involved in manual design procedure. This paper discusses the development of a Computer Aided Design and Drafuing (CADD) of power transmission shafts with multiple design criteria (strength, torsional rigidity, critical speed, Soderberg and lateral rigidity). Visual Basic 2008 was used for the implementation of the algorithm, while Fireworks was used for the development of the Graphical User Interface (GUI). The developed CADD is called UI-CADSHAFT. The software was applied for a typical case study and validated with manual design. Accurate results with increased productivity about twenty folds over the manual design are obtained. The software is fully interactive, user-friendly and runs stand-alone on Microsoft Windows.